If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 9x + -12 Reorder the terms: x = -12 + 9x Solving x = -12 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. x + -9x = -12 + 9x + -9x Combine like terms: x + -9x = -8x -8x = -12 + 9x + -9x Combine like terms: 9x + -9x = 0 -8x = -12 + 0 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 | | ln(x)+ln(x+4)=0 | | 15y-3=29-y | | 17b-8=0 | | x-18+2(x+2)=6x+24 | | 4(4x-1)=2(8x+6) | | 5+4z-3=9z+8-6z | | -3y-2=-5-4y | | 5z+4(4-z)=-(2-4)+10 | | 9+2m=99-8m | | 225=144-24x+x^2+81+18x+x^2 | | 225=144-24x+x^2+81+18x+x | | P=2(96)+2(99) | | 5z+4(4-2)=-(2-4)+10 | | I=(400)(.14)(2) | | 2m^2-5m+2=0 | | 7r+9r=112 | | -144=-9d | | (5x^2-x+2)-(x^2+6x-8)=0 |